Mengurangi cacat spot welding pada proses pembuatan tuas rem belakang type KWBF dengan metode Taguchi di PT. Ciptaunggul Karya Abadi - Azzahra, Salsa Fatima; Nugraha, Iwan; Sumarjo, Jojo (Universitas Muhammadiyah Metro, 2023)
The process of joining the Rear Brake Arm to resistance spot welding or spot welding is known to be found not a few defective products, consequently, it is essential to carry out study with the goal of minimizing defects in the Rear Brake Arm. Then there is still more to be researched concerning the influencet of spot welding parameters, especially the strong current associated with welding heat and plate thickness affecting the mechanical characteristics of spot welding on low carbon steel, in order to know the most appropriate combination of variables between welding current, welding time and plate thickness used. This research uses carbon steel plates (SPCC-SD) with a length of 1000 mm, a width of 200 mm, and a thickness on the plate of 3.2 mm. This research is intended to get the right parameters for the level of welding defects in the spot welding process. Spot welding is welded with the parameters of strong current (A) 7.5; 9.5; 9.9, Welding time (s) 1. 5; 1.7; 19 and load (Kg) 8; 10; 14. The process of improvement with the taguchi method there are two methods, namely the avarage method obtained research results showing that with a strong current of 9.9 amperes, welding time 1.9 second, and a load of 14 kg produces a good percentage of success compared to other variables. The component that is particularly crucial in the process of spot welding on the manufacture of Arm Rear Brake is the strong current. Then the S/N ratio method obtained results that show the smaller the results the better, so the setting of the spot welding machine in the manufacture of Arm Rear Brake with a strong current of 9.9 Ampere, welding time 1.9 second, and welding load of 14 Kg.Based on the Taguchi method researchers can find out the factors that are very influential on the process of Resisntace spot welding or spot welding, namely strong current, welding time, and load. From the results of research using the Taguchi method, the following are the right machine settings in the spot welding process, namely with a current strength of 9.9 Amperes, welding time 1.9 seconds and a load of 14 Kg.